Using literature to enhance writing instruction a guide for K-5 teachers - Olness, Rebecca (Newark, Del. International Reading Association, 2005)
"Rebecca Olness combines her love of children?s literature and her experience as a classroom teacher and literacy specialist to show how to teach content and literacy concepts simultaneously."--Publisher's description.
The reading-writing connection -- Teaching writing and genre literature -- Writing from experience -- Finding good ideas and details -- Organizing ideas -- Expressing feelings through voice -- Choosing the right words -- Apprehending fluency and rhythm -- Editing for conventions -- Some final thoughts.
Keywords: English language -- Composition and exercises -- Study and teaching (Elementary); Reading (Elementary); Children's literature -- Study and teaching (Elementary)